Persepsi Konsumen Terhadap Aspek Bauran Pemasaran (Marketing Mix 4p) Pada Rumah Kopi Tanjung Batu Di Megamas Kota Manado - Sakulat, Stenli; Benu, Noortje Marsellanie; Wariki, Barce A. F. (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2024)
This research aims to determine and describe consumer perceptions of the marketing mix aspects (marketing mix 4P) offered by the Tanjung Batu Coffee House in Megamas, Manado City, which consist of product, price, place, promotion. . The research took place from April to June 2024. The method used in sampling is accidental sampling. The data used is primary data and secondary data. Primary data was obtained directly from consumers of the Tanjung Batu Coffee House in Megamas through interviews using a questionnaire, while secondary data was obtained from the Tanjung Batu Coffee House in Megamas in the form of business history, level of visits, incoming receipts, leadership structure, job descriptions, and types. products offered. The results of the research show that consumer perceptions of the product, price, place, promotion at the Tanjung Batu Megamas Coffee House, overall consumers are satisfied, both from the products offered, the prices set, the place given and promotions given. So that it achieves a total data collection score of 3,823 from the ideal score of 4,500 and shows that the consumer perception measurement index figure reaches 83.63% from 100% in the satisfied category.